Use of DMT and CPTU tests in the evaluation of shear modulus G 0 for soils of different origin - Zbigniew Młynarek; Jędrzej Wierzbicki; Paola Monaco; Katarzyna Stefaniak (Archives of Civil Engineering, 2023)
The subject of this article is the analysis of the relationship between G 0/ M DMT and K D, where G 0 is the small strain shear modulus, while M DMT and K D are respectively the constrained modulus and the horizontal stress index determined from DMT tests. This relationship allows to determine a profile with depth of G 0 from standard DMT test results, useful when data from nonseismic DMT investigations are available. The analysis was based on a large amount of data for a wide range of soils of different origins in Poland. The dataset included OC and NC loams, silts, medium sands, silty sands and fine sands. The overconsolidation ratio (OCR) was estimated using data from CPTU and DMT tests. The obtained empirical G 0/ M DMT vs. K D relationships were compared with the correlations established by Marchetti et al. [1] for different soil types. To account for the significant influence of overconsolidation, an original empirical relationship between G 0/ p and K D, where p is the preconsolidation stress, was defined based on data from all investigated fine-grained soils.